2021
DOI: 10.1016/j.mayocpiqo.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Management During the COVID-19 Pandemic: A Review of Recent Innovations in Antiviral Therapy and Relevance to Primary Care Practice

Abstract: Seasonal influenza requires appropriate management to protect public health and resources. Decreasing the burden of influenza will depend primarily on increasing vaccination rates as well as prompt initiation of antiviral therapy within 48 hours of symptom onset, especially in the context of the current COVID-19 pandemic. A careful approach is required to prevent health services from being overwhelmed by a surge in demand that could exceed capacity. This review highlights the societal burden of influenza and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The epidemiological and clinical characteristics described could be used in hypothesis for further studies to identify the risk factors associated with severe forms of influenza and COVID-19. For example, a further study regarding the impact of antiviral treatment against COVID-19 on the influenza viruses' detection rate is required, as most antivirals used have proven their effectiveness in the treatment of influenza over time [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological and clinical characteristics described could be used in hypothesis for further studies to identify the risk factors associated with severe forms of influenza and COVID-19. For example, a further study regarding the impact of antiviral treatment against COVID-19 on the influenza viruses' detection rate is required, as most antivirals used have proven their effectiveness in the treatment of influenza over time [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…ILI is commonly spread through contact with an infected person (direct or indirect) ( Fauzi et al, 2023 ), with an incubation period of 1–4 days ( Table 1 ) ( Stellrecht, 2017 ). In Saudi Arabia the number of cases infected with ILI is about 1424 from 2018 to 2021 ( MOH, 2021b ), however, the number of cases in the United States is 9 million to 49 million annually ( Spencer et al, 2022 , Jones et al, 2021 ), ( Blanchet Zumofen et al, 2023 ), which is considered a leading factor for high mortality and morbidity ( Mezlini et al, 2022 ). ILI prevention and controlling approaches are vaccination and antiviral medication for treatment ( Blanchet Zumofen et al, 2023 ); yet, vaccination plays a critical role in reducing the prevalence rate internationally and reducing the severity of the infection ( Khan et al, 2021c , Kaaijk et al, 2022 ).…”
Section: Respiratory Viral Infectionsmentioning
confidence: 99%
“…Less than 5% of children develop bacterial sinusitis secondary to influenza virus infection [14]. Sinusitis a frequent complication for those in high-risk groups, especially adults [1]. A research conducted by Peltola VT et al, using animal models has showed that H3N2 subtype gripal viruses are better partners of Streptococcus pneumonia in the induction of secondary bacterial infection such sinusitis [15].…”
Section: Sinusitismentioning
confidence: 99%
“…Influenza which occurs in seasonal epidemics is a public health problem due to its severity and consequences. Seasonal influenza coupled with COVID-19, infection with the virus SARS-CoV2, represents a dual challenge to the primary care [1]. Influenza complications occasionally require absenteeism from school or work, hospitalization, while other times they can cause death.…”
mentioning
confidence: 99%